EFL reading strategies of main idea comprehension and identification: Awareness and use of Arabic speaking university students - Ali Elashhab, Seham (University of Ottawa (Canada), 2008)
This study investigated the effects of reading comprehension strategy awareness and use on main idea comprehension and recall in first and second languages for Arabic-speaking Libyan university students. The research examined the effects of general reading proficiency, text difficulty and topic interest and familiarity on main idea comprehension. The study also examined whether there is a facilitatory relationship between awareness of reading comprehension strategies and their effective use. Participants were all university students majoring in Teaching English as a Second Language (TESL). There were 112 participants from Libya and 16 English speaking control participants from Canada. Reading comprehension strategy awareness was assessed via Mokhtari and Sheorey's (2002) Survey of Reading Strategy. The CanTEST was used to assess the English as a second language reading proficiency of the Arabic-speaking group, while the Nelson-Denny Reading Test served to assess L1 reading proficiency for the English-speaking group. An English reading text was administered to both groups and an Arabic reading text to the Arabic group only. The texts served as the basis for examining the English group's L1 and the Arabic group's L1 and L2 reading comprehension strategy use through their recall of the main ideas of these texts. A reader assessment questionnaire was employed to assess text difficulty, topic interest and familiarity. In addition, semi-structured reading strategy interviews were conducted individually with participants from the control and the experimental groups. The interviewees were randomly selected from within different reading proficiency groupings. Results revealed that reading comprehension strategy awareness had no effect on main idea comprehension in both L1 and L2 for the native Arabic group. The native English group had higher awareness of the three categories of reading strategies (Support, Global and Problem-solving) than the native Arabic group. The Problem solving strategy category was the most familiar to the native Arabic group. Results indicated that general reading proficiency did not affect the recall performance of main ideas for either group. Text difficulty and topic interest did not contribute to the comprehension and recall of main ideas, while topic familiarity was a factor in the recall performance of the native Arabic group. Qualitative analysis of the results indicated that the native English group effectively used more reading strategies than the native Arabic group, and that the native Arabic group did not actually use the strategies which they claimed the highest awareness of. Futhermore, they tended to misapply the strategies that they did use. These findings indicated that simply knowing about reading strategies does not necessarily result in being able to use them appropriately. We concluded that reading strategy awareness alone is not sufficient for the comprehension and recall of main ideas and that awareness needs to be accompanied by effective strategy use in order to have a positive impact on main idea comprehension and recall.
Keywords: Education, Bilingual and Multicultural.; Language, Linguistics.